2011
DOI: 10.5732/cjc.011.10234
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin induces differentiation of glioma stem/progenitor cells by activating autophagy

Abstract: Glioma stem/progenitor cells (GSPCs) are considered to be responsible for the initiation, propagation, and recurrence of gliomas. The factors determining their differentiation remain poorly defined. Accumulating evidences indicate that alterations in autophagy may influence cell fate during mammalian development and differentiation. Here, we investigated the role of autophagy in GSPC differentiation. SU-2 cells were treated with rapamycin, 3-methyladenine (3-MA) plus rapamycin, E64d plus rapamycin, or untreate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…This applies to 1) temozolomide, whose effect on glioblastoma CSCs involves the activation of autophagic cell death, suggesting that the down-regulation of autophagy-related proteins may be a mechanism to evade temozolomide-induced cytotoxicity (Fu et al, 2009); 2) resveratrol, which eliminates breast CSCs by inducing autophagy via the suppression of the Wnt/-b catenin signaling pathway (Fu et al, 2014) or upstream of the activation of apoptosis (Filippi-Chiela et al, 2011) and 3) metformin (a pharmacological agent currently employed for the treatment of type 2 diabetes and known to selectively kill breast CSCs (Hirsch et al, 2009)), which seems to exert its anti-CSC effect by modulating the mTOR signaling pathway (Mohammed et al, 2013). Along similar line, the depletion of DNA-PKcs radiosensitized glioma CSCs by inducing autophagic cell death (Zhuang et al, 2011b), while autophagy activation by the modulation of mTOR activity promoted neuroblastoma and glioma stem cell differentiation and abrogated resistance of glioma stem cells to radiation (Zeng and Zhou, 2008, Zhuang et al, 2011a, Zhuang et al, 2011c. Finally, brain CSCs succumbed to adenovirus-mediated cell death via autophagy, both in vitro and in vivo (Jiang et al, 2007) Reportedly, some drugs may simultaneously trigger distinct pathways of RCD (Galluzzi et al, 2015, Galluzzi et al, 2012.…”
Section: Autophagy Activation In Cscs Affects Therapy Responsementioning
confidence: 78%
“…This applies to 1) temozolomide, whose effect on glioblastoma CSCs involves the activation of autophagic cell death, suggesting that the down-regulation of autophagy-related proteins may be a mechanism to evade temozolomide-induced cytotoxicity (Fu et al, 2009); 2) resveratrol, which eliminates breast CSCs by inducing autophagy via the suppression of the Wnt/-b catenin signaling pathway (Fu et al, 2014) or upstream of the activation of apoptosis (Filippi-Chiela et al, 2011) and 3) metformin (a pharmacological agent currently employed for the treatment of type 2 diabetes and known to selectively kill breast CSCs (Hirsch et al, 2009)), which seems to exert its anti-CSC effect by modulating the mTOR signaling pathway (Mohammed et al, 2013). Along similar line, the depletion of DNA-PKcs radiosensitized glioma CSCs by inducing autophagic cell death (Zhuang et al, 2011b), while autophagy activation by the modulation of mTOR activity promoted neuroblastoma and glioma stem cell differentiation and abrogated resistance of glioma stem cells to radiation (Zeng and Zhou, 2008, Zhuang et al, 2011a, Zhuang et al, 2011c. Finally, brain CSCs succumbed to adenovirus-mediated cell death via autophagy, both in vitro and in vivo (Jiang et al, 2007) Reportedly, some drugs may simultaneously trigger distinct pathways of RCD (Galluzzi et al, 2015, Galluzzi et al, 2012.…”
Section: Autophagy Activation In Cscs Affects Therapy Responsementioning
confidence: 78%
“…The authors suggested that GSCs might not be susceptible to classical pathways of autophagy [ 95 ]. On the other hand, rapamycin induces the differentiation of GSCs by activating autophagy [ 96 , 97 ]. Increased rates and numbers of neurospheres in the rapamycin group compared with other groups were also reported.…”
Section: Chemoresistancementioning
confidence: 99%
“…Increased rates and numbers of neurospheres in the rapamycin group compared with other groups were also reported. Additionally, stem/progenitor cell and differentiation markers were downregulated and upregulated in rapamycin-treated cells, respectively [ 97 ]. These data suggest that apoptosis and autophagy might contribute to GSC chemoresistance.…”
Section: Chemoresistancementioning
confidence: 99%
“…Additionally, sirolimus had a synergistic effect with LY294002, an inhibitor of PI3K, and UCN-01, an inhibitor of AKT [289]. Sirolimus induced autophagy in glioma stem/progenitor cells (GSPCs) and promoted differentiation of such cells both in vitro and in vivo [290]. Rapamycin has also showed synergistic effects with the oncolytic adenovirus OBP-405.…”
Section: Introductionmentioning
confidence: 99%